Evaluation of Factors Associated with Problem Solving and Clinical Decision-Making Skills in Charge Nurses - Seyhan Çerçi; Nermin Uyurdağ; Nuran Reyhanoğlu (Sağlık ve Hemşirelik Yönetimi Dergisi, 2022)
Aim: This study aims determine the perceptions of charge nurses regarding their problem-solving and clinical decision-making skills. Method: In this research, a descriptive and correlational design was employed. The study was conducted with 54 charge nurses who agreed to participate in the study, and the sample of this study consists of charge nurses working in public education and research hospitals in Istanbul and Diyarbakir provinces. The data were collected with 'Descriptive Information Form, Problem Solving Inventory, Clinical Decision-Making Scale in Nursing'. For the data evaluation, the number and percentage were calculated and Mann Whitney U, Kruskal Wallis, and Pearson correlation tests were used. Results: The total mean score of the charge nurses' problem-solving inventory was 61.64+-14.44; the mean score of the clinical decision-making scale was 151.00+-12.99. It was determined that there was a significant difference between the problem-solving skills of the charge nurses and the variables of the place of residence and years of employment (p<0.05). A moderate negative correlation (r=-0.47; p<0.01) was found between the problem-solving skills and clinical decision-making skills of the charge nurses participating in the study. Conclusion: Charge nurses have high problem-solving skills and clinical decision-making skills. The results of this study can provide data to improve skills by making the variables that affect these skills visible.